2016
DOI: 10.3319/tao.2016.03.06.01(aa)
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Study of foF2 Derived from Oblique Sounding Network and Vertical Ionosonde in Northern China

Abstract: The China Seismo-ionospheric Ground-based Monitoring Network in Northern China was established in August 2009, consisting of 5 vertical sounding stations and 20 oblique receiving stations. We analyzed the critical frequency of the F2 region (foF2) derived from vertical and oblique sounding data in this study. Our comparison results indicated that foF2 from vertical and oblique sounding presented very similar annual and semi-annual variation characteristics and along with the change in F 10.7 , the two data bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Using these data, some perturbations were found before the Nepal M s 8.1 earthquake on 25th April 2015. Another is the China Seismo‐ionospheric Ground‐based Monitoring Network (CSGMN) in Northern China (Liu J et al, 2016b). It was found that oblique sounding data present similar change characteristics to those seen in vertical sounding data.…”
Section: Ionospheric Dynamicsmentioning
confidence: 99%
“…Using these data, some perturbations were found before the Nepal M s 8.1 earthquake on 25th April 2015. Another is the China Seismo‐ionospheric Ground‐based Monitoring Network (CSGMN) in Northern China (Liu J et al, 2016b). It was found that oblique sounding data present similar change characteristics to those seen in vertical sounding data.…”
Section: Ionospheric Dynamicsmentioning
confidence: 99%
“…Using vertical/slant ionosounding, Pulinets and Boyarchuk (2004) [9] presented the first comprehensive study of F2 layer critical frequency (foF2) anomalies observed before strong earthquakes. [10] carried out a comparative study of foF2 anomalies in northern China using an oblique sounding network and a vertical ionosonde. It was shown that these anomalies exhibited similar characteristics and could be used to investigate seismoionospheric effects.…”
Section: Introductionmentioning
confidence: 99%